VD_FINDINFO Arrêt / 2022 / 578 vom 20. Juli 2022 - VD Tribunal cantonal (2022)
REJET DE LA DEMANDE, DROIT D'ÊTRE ENTENDU, COMPÉTENCE RATIONE LOCI | 416 al. 1 ch. 1 CC, 416 al. 1 ch. 5 CC, 442 al. 1 CC, 442 al. 5 CC, 29 al. 2 Cst.